Static dielectric function of a model classical ionic fluid - Gurbuz, H; Tasseven, C; Silbert, M (GORDON BREACH SCI PUBL LTD, 1996)
The behaviour of the static dielectric function epsilon(k) of a system of charged hard spheres has been studied, within the Mean spherical Approximation, for a wide range of values of the ionic size ratio alpha, packing fraction eta, and plasma parameter Gamma. The results presented are limited to the charge symmetric case. We find that epsilon(k) already takes on negative values for Gamma = 1 when the size of anions and cations are the same and eta = 0.30. Packing and size difference become less significant as the value of the plasma parameter increases. As Gamma increases in value epsilon(k) becomes negative over an increasing range of values of the wavenumber k. For given values of Gamma and eta, epsilon(k) is nearest to zero for a non-zero value of k when alpha = 1.0.
Keywords: static dielectric function; charged hard spheres; ASYMMETRIC ELECTROLYTES; MOLECULAR-DYNAMICS; HALIDES; AGI; Chemistry; Physics